(untitled) (Journal of Music Research Online, 2022)
The literature on the role of double bass players has predominantly focused on musical practices which reflect the tradition of swing and the walking bass lines. The performance practices of contemporary jazz musicians, however, are far more diverse and reflective of the music’s hybridity. Taking as a case study Lloyd Swanton, double bassist with acclaimed Australian trio The Necks, I explore the ways that double bass players have reimagined the roles and sound of the double bass. I argue that the development of Swanton’s musical practices goes hand in hand with the changes to traditional jazz ensemble roles that occur in the group which open up space for innovative performance practices which reimagine the sound of the instrument.